The relationship between positive thinking and self-confidence among secondary school - Haider hadi , Assist. Lect . Sura (Basra studies journal, 2026)
The current study seeks to measure the relationship between positive thinking and self-confidence among female high school students and to determine whether a person possesses positive thinking and whether this is reflected in their self-confidence, according to the female-only variable. The researcher adopted the Positive Thinking Scale ( Ibrahim 2021), consisting of (51) items, and the Self-Confidence Scale (Jabari 2023) which consisting of (36) items. The two scales were applied to the research sample that was randomly selected, the number of participated female students was (100) students and it included all levels of intermediate and preparatory school. The results showed that the Pearson correlation coefficient was used by the sample. The analysis results showed that the relationship between positive thinking and self-confidence was negative (-0.08753). This result indicates that there is a very slight inverse relationship between the two variables, there is no real or statistically significant correlation between positive thinking and self-confidence in the studied sample.